2019
DOI: 10.1016/j.ijplas.2019.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation dynamics formulation for self-climb of dislocation loops by vacancy pipe diffusion

Abstract: It has been shown in experiments that self-climb of prismatic dislocation loops by pipe diffusion plays important roles in their dynamical behaviors, e.g., coarsening of prismatic loops upon annealing, as well as the physical and mechanical properties of materials with irradiation. In this paper, we show that this dislocation dynamics self-climb formulation that we derived in Ref.[1] is able to quantitatively describe the properties of self-climb of prismatic loops that were observed in experiments and atomist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 69 publications
(242 reference statements)
4
25
0
Order By: Relevance
“…We validate our phase field model by numerical simulations and comparisons with the DDD simulation results obtained in Ref. [13] and available experimental observations. The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…We validate our phase field model by numerical simulations and comparisons with the DDD simulation results obtained in Ref. [13] and available experimental observations. The rest of the paper is organized as follows.…”
Section: Introductionmentioning
confidence: 54%
“…In Ref. [13], a numerical implementation method of this self-climb formulation for discrete dislocation dynamics (DDD) was proposed, and simulations were performed on evolution, translation, coalescence and other self-climb motions of prismatic loops that are in excellent agreement with experimental and atomistic results. It has also been shown that this self-climb formulation is able to quantitatively explain the annihilation of prismatic loops with free surfaces by dislocation self-climb observed in molecular dynamics simulations [16] and self-healing of low angle grain boundaries by vacancy diffusion [17].…”
Section: Introductionmentioning
confidence: 87%
See 3 more Smart Citations